IMPROVEMENT OF POETRY WRITING SKILLS BY USING CLUSTERING TECHNIQUE OF CLASS VIII STUDENTS OF SMP NEGERI 3 ALLA, ENREKANG DISTRICT - Hernita Arifuddin (Celebes Education Review, 2019)
Abstract This research is a classroom action research which aims to improve poetry writing skills for class VIII students of SMP Negeri 3 Alla through clustering techniques. The subjects of this study were class VIII of State Junior High School 3 Alla who were enrolled in the 2011/2012 school year with 34 subjects. This research was conducted in 2 (two) cycles and each cycle was carried out in four meetings including the final test for each cycle. Data on student learning outcomes were analyzed by using quantitative analysis and data on student activities were analyzed by using qualitative analysis. The results of the study after the implementation of the action for two cycles, namely: (a) Increased poetry writing skills of students of class VIII.1 SMP Negeri 3 Alla after clustering techniques were applied in which in the first cycle obtained an average score of 58.82% in the medium category but have not yet achieved the minimum completeness criteria for writing poetry that is determined and experienced an increase in the second cycle of 73.23% in the high category and has achieved the minimum specified completeness criteria. From the results of this study it can be concluded that the clustering technique can improve poetry writing skills of class VIII students of SMP Negeri 3 Alla, Enrekang Regency. Keyword: Learning Outcomes, Clustering Techniques